2007
DOI: 10.1111/j.1524-4725.2007.33352.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Smooth-Gel Hyaluronic Acid Dermal Fillers with Cross-linked Bovine Collagen: A Multicenter, Double-Masked, Randomized, Within-Subject Study

Abstract: The smooth-gel HA dermal fillers offer longer-lasting correction than bovine collagen-which may lessen the frequency that repeat treatments are needed. Also, they were preferred by the vast majority of subjects-which should promote patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 5 publications
2
117
0
2
Order By: Relevance
“…Pain and bruising are frequent and increase with the viscosity of the filler [52,53]. A too superficial injection as well as an insufficient posttreatment massage in terms of product distribution in the tissue can increase the risk for temporary skin induration [54,55] and nodules [6,39].…”
Section: Adverse Events Related To Temporary Fillersmentioning
confidence: 99%
“…Pain and bruising are frequent and increase with the viscosity of the filler [52,53]. A too superficial injection as well as an insufficient posttreatment massage in terms of product distribution in the tissue can increase the risk for temporary skin induration [54,55] and nodules [6,39].…”
Section: Adverse Events Related To Temporary Fillersmentioning
confidence: 99%
“…6-7). Different studies agree (1,(20)(21)(22)(23)84) that the mean duration of HA, regardless of the type and brand, is multifactorial and also depends on:…”
Section: A B C Dmentioning
confidence: 99%
“…The following classifications were also used in the postimplant check-ups: WSRS, as well as the patient and investigator Global Aesthetic Improvement Scale (GAIS): 1 to 5; and the Patient Satisfaction Scale (PSSS): -2 to + 2. (19)(20)(21)(22) . Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We observed very large differences in the occurrence rate of complications with semi-permanent tissue fillers, between 0 and 56% (TABLE 3). Some authors did not specify the number of complications observed [25][26][27][28]201]. Moreover, in some cases the complications were described per injection site instead of per participant [29,202,203].…”
Section: Semi-permanent Tissue Fillersmentioning
confidence: 99%
“…Most mild or moderate adverse events, in 1 subject an abscess was reported after 4 months Treatment related [27,201] Prospective study (n = 56), 6 months follow-up…”
Section: Hyaluronic Acid (Cross-linked)mentioning
confidence: 99%